Methods of eliminating phonetic interference in teaching English in grades 1-4 through audio exercises - Djurayeva Shahnoza Abduhalilovna (Euro Asian Journal Publishing, 2023)
This article explores various methods and strategies that incorporate audio exercises to eliminate phonetic interference and foster a more immersive language learning experience.
Keywords: English language science; phonetic interference; audio exercises